Development of Handouts Equipped with Glossary of Protista Materials for Class X High School Students - Dini Hari Marta; Dezi Handayani; Anizam Zein (ATRIUM PENDIDIKAN BIOLOGI, 2016)
The purpose of this study was to develop a handout included a glossary on protists  material for class X SMA that is valid and practical. The type of this research is the development research  that uses three phases of  4D model that consisting of define phase (definition), design (design), and develop (development), the fourth phase is  phase of disseiminate (deployment) is not done. This handout is validated by 5 validators, for the practicalities conducted by two teachers and 30 students of  class X IPA 2 SMAN 7 Sijunjung. The data of this research is primary data that is  obtained from the questionnaire validity and practicalities, then analyzed with descriptive analysis. Handout generated from terms of content feasibility, language, presentation, and  chart has an average value of 84.17% and categorized (valid). Handout that is  produced called  practically by teacher  if the average value is  89.58% (practical) and  has been produced by students with 83.91% (practical) of average value.